Hubungan Kemampuan Membaca Kritis dengan Kemampuan Menulis Argumentasi Siswa Kelas VIII SMPN 3 Pariaman - Yulianda, Rika; Agustina, Agustina; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was to see the results of the following descriptions. First, the ability to read critically VIII Junior High School students in grade 3 Pariaman. Second, the ability to write arguments class VIII students of SMP Negeri 3 Pariaman. Third, the relationship of critical reading skills with the ability to write arguments class VIII students of SMP Negeri 3 Pariaman. Data of this study, namely the ability to read critically VIII Junior High School students in grade 3 Pariaman and the ability to write arguments VIII Junior High School students in grade 3 Pariaman. The research data obtained through the test of critical reading skills and the ability to write arguments class VIII students of SMP Negeri 3 Pariaman. Data was collected using correlational research methods. The study's findings that there is a significant relationship between critical reading skills with the ability to write arguments class VIII students of SMP Negeri 3 Pariaman. Difference is seen in the 0.05 significance level with degrees of freedom n-2 that is obtained is tcount ttable = 3.9832 and 1.70 in the sense tcount greater than ttable.